The Research on Security Technology for Low-Performance Iot Sensor Node - Ju, Youngkwan; Jin Mun, Hyung (International Journal of Engineering and Technology, 2018)
Background/Objectives: IoT developmental background: IoT, which is the key technology in the fourth industrial revolution, utilizes the Internet. Particularly, the growth of convergence products that utilize it has been constant with the demands of IoT services using the network of the Internet.Methods/Statistical analysis: IoT network consists of products equipped with various sensors to communicate; sensor nodes are made up of low volume memory, low performance CPU, and battery when they are used in the network. There has been the demand of secure transmission of information measured by a sensor node to the IoT platform. We conduct a study on how we can improve security in the IoT environment.Findings: Generally, sensor nodes are applied with basic security provided by IoT communication protocol rather than their own encryption. Therefore, sensor nodes are vulnerable in terms of security and the IoT platform that utilizes information collected by them would process distorted information.In order to draw a strategy to prevent security breach, we analyze security threat and the type of attacks.Improvements/Applications: We suggest a countermeasure to deal with security threat of sensor nodes and situations in which sensor nodes are vulnerable in IoT environment. To secure integrity of communication and transaction between a sensor node and an IoT platform in the future, the application of block chain technology into the IoT environment is necessary.Â